Exploring the contingent role of 4B’s marketing mix towards customers’ attitude - Eko Agus Susilo; Cahya Nova Kurniawan; Christina Clariza Avianty (University of Merdeka Malang, 2023)
Modern consumers regard social media as a reference group through which they can meet their demands by trading-up purchases for the purpose of recognition in reference groups. Limited edition products are those that take advantage of consumer requirements in this way. Consumers have a more favorable view toward a brand the more closely their self-image and the brand image aligned. The purpose of this study is to examine the 4B marketing mix including Best, Bargaining, Buffer Stocking, and Bombarding towards customer attitude in the context of footwear. Using a quantitative explanatory approach, the sample of this study is 97 people who are consumers of footwear with the Converse Brand in Malang City. The research instrument used an online questionnaire and was analyzed using descriptive analysis and inferential analysis using SPSS version 25. The findings showed that the variables Best, Bargaining, Buffer Stocking, and Bombarding were able to influence customers' attitudes towards Converse footwear consumers in Malang. It is hoped that through these findings, the Converse brand will increase the dissemination of information regarding product quality and retailer capabilities as well as marketing optimization in strengthening consumer perceptions regarding the brand.